About the project of the Lithuanian Education Act of 2001 12 10 - Jovaiša, Leonas (Acta Paedagogica Vilnensia, 2002)
The project of the Lithuanian Education Act as of 10/12/2001 is much more favourable than the law, which is in force today. Nevertheless, many things are to be improved. Particularly, some terms that are foreign for Lithuanian educational terminology. Defining the education system is defined as a control point (service) is unacceptable. In Lithuania, the schools and other education bodies are usually called as cultural institutions.